TANTANGAN PENEGAKAN HUKUM DAN PROSES PERADILAN YANG LAMBAT DALAM MENDORONG INVESTASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Gunawan Widjaja (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study examines the challenges of law enforcement and slow judicial processes in the context of promoting investment and economic growth in Indonesia through a literature review. Although law enforcement is an important pillar for creating certainty and justice, various obstacles such as corruption, limited human resources, complex regulations, and political intervention have led to weak law enforcement. In addition, protracted judicial processes worsen the investment climate by causing uncertainty and high additional costs for business actors. This study highlights the significant impact of these obstacles on investment decisions and national economic performance. The results of the study emphasise the need for comprehensive reforms in the legal and judicial systems, including eradicating corruption, increasing the capacity of law enforcement officials, simplifying regulations, and utilising information technology to accelerate the resolution of disputes. Thus, this study provides an important theoretical basis to support policies that increase legal certainty and judicial efficiency as key factors in promoting a healthy investment climate and sustainable economic growth in Indonesia.